PENINGKATAN LITERASI TEKNOLOGI FINANSIAL BAGI SANTRI PONDOK PESANTREN AL-QUR’AN AL-AMIN PABUARAN - Ratu Ayu Sri Wulandari MA; Krisnhoe Rachmi Fitrijati (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2022)
Rapid technological developments encourage the emergence of technology in the financial sector known as financial technology (fintech). Using fintech by business actors is considered more efficient and effective in the transaction process. Islamic boarding school students are one of the potential users of fintech. However, based on the preliminary survey, the literacy level of students related to fintech still needs to be higher, so it still needs to be held outreach about fintech. This program aims to increase the level of students' understanding of financial technology. The target audience is the students of Al-Amin Pabuwaran Al-Qur'an Islamic Boarding School, North Purwokerto, Banyumas. Based on the results of the evaluation at the end of the training session, provides evidence that there is an increase in students' understanding of fintech, and it is hoped that they can use or utilize existing platforms properly and wisely.